3‐D Reconstruction of Neurons from Multichannel Confocal Laser Scanning Image Series. Issue 1 (10th April 2014) - Wouterlood, Floris G.
Abstract: A confocal laser scanning microscope (CLSM) collects information from a thin, focal plane and ignores out‐of‐focus information. Scanning of a specimen, with stepwise axial ( Z ‐) movement of the stage in between each scan, produces Z ‐series of confocal images of a tissue volume, which then can be used to 3‐D reconstruct structures of interest. The operator first configures separate channels (e.g., laser, filters, and detector settings) for each applied fluorochrome and then acquires Z ‐series of confocal images: one series per channel. Channel signal separation is extremely important. Measures to avoid bleaching are vital. Post‐acquisition deconvolution of the image series is often performed to increase resolution before 3‐D reconstruction takes place. In the 3‐D reconstruction programs described in this unit, reconstructions can be inspected in real time from any viewing angle. By altering viewing angles and by switching channels off and on, the spatial relationships of 3‐D‐reconstructed structures with respect to structures visualized in other channels can be studied. Since each brand of CLSM, computer program, and 3‐D reconstruction package has its own proprietary set of procedures, a general approach is provided in this protocol wherever possible. Curr. Protoc. Neurosci 67:2.8.1‐2.8.18. © 2014 by John Wiley & Sons, Inc.